Current Alcohol Use and Mental Health of Adolescents Among Secondary School Students in Nakuru County, Kenya. - Oteyo, John S.; Mwenje, Margaret (Journal of special needs and disabilities studies, 2013)
Adolescents engage in behaviours that compromise their health and futurepotentials. However, these behaviours are preventable. The current study was designed to establish the association between current alcohol use and the mental health state of secondary school students in Nakuru County, Kenya. Multi-stage cluster, stratified proportionate and simple random samplingmethods were used to selectparticipating divisions (n=6), schools (n=14) and students (n=1000). Global School based Health Survey (GSHS) was used to collect data on health risk behaviours. Sixteen percent (n=161) of students reported use of alcohol 30 days prior to the survey and of these 23.6 (n=38) and 32.9% (n=53) reported a low state of mental health and had seriously considered attempting suicide.The study established that an alcohol drinker was 1.3 (95% C.I: 1.282-1.878) times likely to report a low state of mental health than an alcohol abstainer. A co-occurrence between adolescents' mental health and alcohol use provide an opportunity to draw together separate areas of research in designing a comprehensive approach that may promote better health and education outcomes in secondary schools.
Journal Articles
Keywords: Adolescents; co-occurrence; Current alcohol use; Mental health; health risk behavior